A pack a day for 20 years: smoking and cigarette pack sizes - Farrell, L.; Fry, T.; Harris, Mark (Taylor & Francis, 2011)
This study focuses on the determinants of cigarette consumption. Inparticular, the impact of cigarette pack sizes on the typical dailyconsumption of smokers is investigated. Results are presented from anew multi-modal count data model which allows for ‘pack-effects’ in dailyconsumption levels. Our results suggest that smokers regulate theirconsumption in accordance with the variety of pack sizes that are availableto them.